(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the significant impact of Corporate Social Responsibility (CSR) on brand perception, highlighting its importance in today’s consumer-driven marketplace. As societal expectations shift, consumers increasingly prioritize ethical considerations and sustainability when choosing brands. CSR encompasses various initiatives aimed at addressing social, environmental, and economic challenges, thus reflecting a company’s commitment to operating responsibly. Research indicates that brands actively engaged in CSR are often perceived more favorably by consumers, who associate such initiatives with trustworthiness, integrity, and a genuine concern for societal welfare. This favorable perception can enhance brand loyalty, as consumers are more likely to support companies that align with their values and demonstrate social consciousness. Furthermore, CSR initiatives can differentiate a brand in a competitive landscape, serving as a critical factor influencing consumer choice. Companies like Patagonia and TOMS have successfully built strong identities around their commitment to social and environmental causes, which resonate deeply with their target audiences. The emotional connection fostered through authentic CSR efforts can lead to increased customer advocacy and word-of-mouth promotion, further enhancing brand reputation.